2000
DOI: 10.1074/jbc.m004044200
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Characterization of Synthetic HIV-1 Vpr That Transduces Cells, Localizes to the Nucleus, and Induces G2 Cell Cycle Arrest

Abstract: Human immunodeficiency virus (HIV)Vpr contributes to nuclear import of the viral pre-integration complex and induces G 2 cell cycle arrest. We describe the production of synthetic Vpr that permitted the first studies on the structure and folding of the full-length protein. Vpr is unstructured at neutral pH, whereas under acidic conditions or upon addition of trifluorethanol it adopts ␣-helical structures. Vpr forms dimers in aqueous trifluorethanol, whereas oligomers exist in pure water.1 H NMR spectroscopy al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
134
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(139 citation statements)
references
References 49 publications
3
134
2
Order By: Relevance
“…The necrotic region may result from the changes in cells via a combination of endogenous and Vpr-induced cytotoxicity. As Vpr has been shown to enter cells (Henklein et al, 2000;Sherman et al, 2001;Nakamura et al, 2002), it is possible that the necrotic regions may result from spreading of Vpr from the site of inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…The necrotic region may result from the changes in cells via a combination of endogenous and Vpr-induced cytotoxicity. As Vpr has been shown to enter cells (Henklein et al, 2000;Sherman et al, 2001;Nakamura et al, 2002), it is possible that the necrotic regions may result from spreading of Vpr from the site of inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…First, we introduced a plasmid DNA encoding Vpr or its control plasmid DNA, but it was not possible to assess the effects of Vpr correctly because transfection of plasmid DNA by itself influenced the rate of HR (data not shown). It has been well reported that Vpr enters cells and expresses its biological activity when added to the cell culture (Jenkins et al, 1998;Henklein et al, 2000;Huang et al, 2000;Taguchi et al, 2004). These observations encouraged us to perform the experiments by adding Vpr to cells exogenously with subsequent measurement of GFP-positive cells.…”
Section: Increased Rate Of Hr By Vprmentioning
confidence: 95%
“…The majority of amino acid residues of the inner core of the protein could not be assigned because of broadening and overlap of the NMR signals (20). We interpreted these phenomena as arising from the internal tendency of sVpr to undergo self-association in aqueous solution.…”
mentioning
confidence: 99%
“…However, the design of effective Vpr antagonists requires more detailed knowledge of its dynamic structure and folding during heterologous and homologous protein-protein interactions. In our previous work (20) we have characterized the effect of the solution conditions on the folding and self-association of synthetic full-length Vpr (sVpr), and initial information on the secondary structure of sVpr was obtained by CD spectroscopy (20). In these studies we were able to demonstrate that both the secondary structure of sVpr and its folding, as well as its tendency to undergo protein-protein interaction, critically depend upon the solution parameters such as pH and hydrophobicity.…”
mentioning
confidence: 99%
See 1 more Smart Citation